UPAYA PEMBERANTASAN PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA MELALUI PROGRAM KEREN (KADER EDUKATIF ANTI NARKOBA) OLEH BNN - Dodon (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
“KEREN” is a place for cadre of Educative Anti-Drug Cadres with various professional backgrounds (Trainers, Lecturers, Directors, Principals, Teachers, Ustadz, Entrepreneurs, Students, Students, etc.) who have a strong commitment to save and nurture the nation's generation and optimize the potential to assist BNN in eradicating Drug abuse in Indonesia. The purpose of this research is to know the effort of eradication of drug abuse among adolescent through KEREN program by BNN. The results showed that 1) Eradication of drug abuse among adolescents conducted BNNP East Java by launching the program KEREN (Cadres Edukatif Anti Drug) as a container to run anti-drug socialization activities and healthy life without drugs in schools targeting among adolescents. 2) Activity KEREN then share some things with students and schools, namely: first, introduce the BNN function. Second, share the tips of success and solve the problem without drugs. Third, schools should establish cooperative relationships with communities around the school.